A clinical study on the efficacy of Yiqi Huayu Jiedu decoction for reducing the risk of postoperative recurrence and metastasis of gastric cancer: Protocol for a multicenter, randomized, double-blind, placebo-controlled trial. Issue 48 (25th November 2020) - Wu, Cun-En; Xue, Wei-Wei; Zhuang, Yu-Wen; Ding, Da-Wei; Zhou, Jin-Yong; Liu, Shen-Lin; Wang, Rui-Ping; Shu, Peng
Abstract: Background: Gastric cancer (GC) is one of the top 10 malignant tumors worldwide and poses a great threat to human life and health, the prevention and treatment of which has become the focus and difficulty of medical research. With its unique advantages, traditional Chinese medicine (TCM) is widely used in the prevention and treatment of postoperative recurrence and metastasis of GC as well as the improvement of patients' quality of life. The aim of this study is to elucidate the curative effect and the underlying mechanism of Yiqi Huayu Jiedu (YQHYJD) decoction. Methods/design: This is a prospective, multicenter, randomized controlled trial continuing 3 years. Two hundred ninety-eight eligible patients will be randomly divided into 2 groups, the chemotherapy combined with placebo and the chemotherapy combined with YQHYJD group at a ratio of 1:1. All patients will receive the treatment for 6 months and follow up for 3 years. The primary outcomes are disease-free survival, and 1-year, 2-year, 3-year progression-free survival rate, while the secondary outcomes are tumor makers, TCM syndrome score, quality of life score, overall chemotherapy completion rate, intestinal flora diversity test, immune function (T, B lymphocyte subsets and NK cells) test. The Security index includes blood, urine and stool routine, electrocardiogram, liver function (ALT), and renal function (BUN, Scr). All of these outcomes will be analyzed at the end of the trial. Discussion: This research will provide the valuable evidence for the efficacy and safety of Yiqi Huayu Jiedu decoction in postoperative GC. Furthermore, it will be helpful to form a higher level of evidence-based medical basis for TCM in the treatment of GC recurrence and metastasis. Trial registration: ChiCTR2000039038